Dabigatran, Rivaroxaban, or Apixaban versus Warfarin in Patients with Nonvalvular Atrial Fibrillation: A Systematic Review and Meta-Analysis of Subgroups. (22nd December 2013) - Gómez-Outes, Antonio; Terleira-Fernández, Ana Isabel; Calvo-Rojas, Gonzalo; Suárez-Gea, M. Luisa; Vargas-Castrillón, Emilio
Abstract : Background . New oral anticoagulants (NOAC; rivaroxaban, dabigatran, apixaban) have become available as an alternative to warfarin anticoagulation in non-valvular atrial fibrillation (NVAF). Methods . MEDLINE and CENTRAL, regulatory agencies websites, clinical trials registers and conference proceedings were searched to identify randomised controlled trials of NOAC versus warfarin in NVAF. Two investigators reviewed all studies and extracted data on patient and study characteristics along with cardiovascular outcomes. Relative risks (RR) and 95% confidence intervals (CI) were estimated using a random effect meta-analysis. Results . Three clinical trials in 50, 578 patients were included. The risk of non-hemorrhagic stroke and systemic embolic events (SEE) was similar with the NOAC and warfarin (RR = 0.93 ; 95%CI = 0.83 –1.04), while the risk of intracranial bleeding (ICB) with the NOAC was lower than with warfarin (RR = 0.46; 95% CI = 0.33–0.65). We found differences in the effect size on all strokes and SEE depending on geographic region as well as on non-hemorrhagic stroke, SEE, bleeding and mortality depending on time in therapeutic range. Conclusion . The NOAC seem no more effective than warfarin for prevention of nonhemorrhagic stroke and SEE in the overall NVAF population, but are generally associated with a lower risk of ICB than warfarin.